Kebijakan Pemerintah dalam Pendidikan Inklusi pada Anak Usia Dini: Government Policy on Inclusive Education for Early Childhood - Ratna, Asmil (Universitas Ngudi Waluyo, 2025)
This article discusses the policy decision by the government in declaring inclusive education for early childhood. Inclusive education as an educational service system aimed at all children including children with special needs. This study is important to be studied because of the existence of an inclusive education policy. This type of research uses the SLR (Literature Review Study) method. The purpose of the research review is to conceptualize the research basis and framework of thought regarding problems in inclusive education. Research articles must meet the following criteria: a) the subject of the research is early childhood; b) inclusive education in Indonesia. This article finds that in Indonesia, the initial steps towards inclusive education have begun in 2000 through an integrated education program. As a policy taken, the government ensures that educational services are adjusted to the 1945 Constitution. This policy is based on several important policies, including Law Number 4 of 1997 concerning Persons with Disabilities, Law Number 23 of 2002 concerning Child Protection, Government Regulation Number 19 of 2005 concerning National Education Standards, Regulation of the Governor of DKI Jakarta Number 116 of 2007 concerning the Implementation of Inclusive Education. Although policies and regulations already exist, the implementation of inclusive education still faces many obstacles, including the unpreparedness of institutions, lack of understanding and special training for teachers and inadequate facilities and infrastructure in many schools. ABSTRAK Artikel ini membahas mengenai keputusan kebijakan oleh pemerintah dalam mendeklarasikan pendidikan inklusi pada anak usia dini. Pendidikan inklusif sebagai sistem layanan pendidikan yang ditujukan kepada semua anak termasuk anak berkebutuhan khusus. Studi ini penting untuk diteliti karena adanya suatu kebijakan pendidikan inklusif. Jenis penelitian ini menggunakan metode SLR (Studi Literature Review). Tujuan dari tinjauan penelitian ialah untuk mengonsepkan landasan penelitian dan kerangka pemikiran mengenai permasalahan dalam pendidikan inklusi. Artikel penelitian harus memenuhi kriteria berikut: a) subyek penelitian adalah anak usia dini; b) pendidikan inklusi di Indonesia. Artikel ini menemukan bahwa di Indonesia, langkah awal menuju pendidikan inklusif telah dimulai pada tahun 2000 melalui program pendidikan terpadu. Sebagaimana kebijakan yang diambil, pemerintah memastikan bahwa layanan pendidikan disesuaikan dengan Undang-Undang Dasar 1945. Kebijakan tersebut dilandasi dengan beberapa kebijakan penting, termasuk UU Nomor 4 Tahun 1997 tentang Penyandang Cacat, UU Nomor 23 Tahun 2002 tentang Perlindungan Anak, Peraturan Pemerintah Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan, Peraturan Gubernur DKI Jakarta Nomor 116 Tahun 2007 tentang Penyelenggaraan Pendidikan Inklusif. Meskipun kebijakan dan regulasi sudah ada, penerapan pendidikan inklusif masih menghadapi banyak kendala, termasuk ketidaksiapan lembaga, kurangnya pemahaman dan pelatihan khusus bagi guru serta sarana prasarana yang belum memadai di banyak sekolah.